2013
DOI: 10.12988/ams.2013.13183
|View full text |Cite
|
Sign up to set email alerts
|

A validation of profit sharing ratio determination mathematical model for Islamic hire-purchase contract

Abstract: This paper discusses the mathematics formulation of determining the profit sharing ratio for Islamic hire-purchase contract named Al-Ijarah Thumma Al-Bai' or AITAB. This paper presents an approach which maximizes the profits of the hire-purchase participating parties by implementing the fair profit sharing ratio determination mentioned in the profit sharing concept with stochastic optimization technique. Then the validation of the model is also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Cluster 1 talks a lot about contracts and practices in Islamic banking, in particular the scheme and modeling of profit-loss sharing, both mudharabah, and musyarakah. Some modeling related to the PLS scheme, among others, was carried out by Bakhtiar et al (2014), Halim (2013, Halim et al (2016), Hasan (2010), Khaled & Khandker (2015), Sugema et al (2010), Sumarti & Marendri (2017), Sumarti et al (2015), Wahyudi & Sakti (2016) and Wolf et al (2018). Meanwhile, specifically, the mudharabah profit-sharing modeling has been carried out by Cahyandani et al (2017), Isa (2011), andOmar &Jaffar (2016).…”
Section: Visualization Of Network Co-word Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster 1 talks a lot about contracts and practices in Islamic banking, in particular the scheme and modeling of profit-loss sharing, both mudharabah, and musyarakah. Some modeling related to the PLS scheme, among others, was carried out by Bakhtiar et al (2014), Halim (2013, Halim et al (2016), Hasan (2010), Khaled & Khandker (2015), Sugema et al (2010), Sumarti & Marendri (2017), Sumarti et al (2015), Wahyudi & Sakti (2016) and Wolf et al (2018). Meanwhile, specifically, the mudharabah profit-sharing modeling has been carried out by Cahyandani et al (2017), Isa (2011), andOmar &Jaffar (2016).…”
Section: Visualization Of Network Co-word Mapsmentioning
confidence: 99%
“…Halim and Jaffar generally researched and carried out mathematical modeling for PLS schemes both in banks and other financial institutions. The difference, Halim conducted a study on the application of the ijarah muntahiya bittamlik scheme or the AITAB contract (Halim et al 2012;Halim et al, 2016;Halim, 2013) while Jaffar more demonstrated the PLS model in the musyarakah transaction agreement (Jaffar et al, 2017; and mudharabah (Omar & Jaffar, 2016) or both (Jaffar & Issa, 2011).…”
Section: Visualization Of Density Maps Co-authormentioning
confidence: 99%
“…A similar topic was studied by Dale-Johnson [37]. Halim and Jaaman [38] developed a mathematical model for a specific type of contract, named AITAB. McCann and Ward [39] analyzed rental payments using a multi-period stock inventory model and showed that the factor that most influences the tenant's value of the land is the duration of the lease.…”
Section: Literature Reviewmentioning
confidence: 99%